+0  
 
0
619
2
avatar

2^3x-1=(1\8)^x

Guest Mar 4, 2015

Best Answer 

 #2
avatar+27246 
+5

If this is

 

$$2^{3x-1}=(\frac{1}{8})^x$$

 

then rewrite it as

 

$$\\2^{3x-1}=(\frac{1}{2^3})^x\\\\2^{3x-1}=(2^{-3})^x\\\\2^{3x-1}=2^{-3x}$$

 

So we must have

 

$$\\3x-1=-3x\\\\6x=1\\\\x=\frac{1}{6}$$

.

Alan  Mar 4, 2015
 #1
avatar+47 
0

x=8^(-x-1)*((8^x)+1)

MILAN6030  Mar 4, 2015
 #2
avatar+27246 
+5
Best Answer

If this is

 

$$2^{3x-1}=(\frac{1}{8})^x$$

 

then rewrite it as

 

$$\\2^{3x-1}=(\frac{1}{2^3})^x\\\\2^{3x-1}=(2^{-3})^x\\\\2^{3x-1}=2^{-3x}$$

 

So we must have

 

$$\\3x-1=-3x\\\\6x=1\\\\x=\frac{1}{6}$$

.

Alan  Mar 4, 2015

22 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.